Remission of a case of multiple Hymenoptera stings‐associated chronic urticaria during venom immunotherapy. Issue 5 (19th May 2021) - Dubini, Marco; Pravettoni, Valerio; Rivolta, Federica; Segatto, Giulia; Asero, Riccardo; Montano, Nicola
Abstract: Hymenoptera stings mostly cause acute urticaria but we describe a case of CU after wasp stings which remitted during venom immunotherapy. IgE‐mechanisms have not been fully clarified in CU, except for isolated circumstances. In our case immunotherapy has played a positive role reducing immune cells reactivity and improving urticaria symptoms. Abstract : Hymenoptera stings mostly cause acute urticaria but we describe a case of CU after wasp stings which remitted during venom immunotherapy. IgE‐mechanisms have not been fully clarified in CU, except for isolated circumstances. In our case immunotherapy has played a positive role reducing immune cells reactivity and improving urticaria symptoms.